Clinical, biochemical and molecular analysis of 13 Japanese patients with β‐ureidopropionase deficiency demonstrates high prevalence of the c.977G > A (p.R326Q) mutation. Issue 5 (14th February 2014) - Nakajima, Yoko; Meijer, Judith; Dobritzsch, Doreen; Ito, Tetsuya; Meinsma, Rutger; Abeling, Nico G. G. M.; Roelofsen, Jeroen; Zoetekouw, Lida; Watanabe, Yoriko; Tashiro, Kyoko; Lee, Tomoko; Takeshima, Yasuhiro; et al.
Abstract: β‐ureidopropionase (βUP) deficiency is an autosomal recessive disease characterized by N‐carbamyl‐β‐amino aciduria. To date, only 16 genetically confirmed patients with βUP deficiency have been reported. Here, we report on the clinical, biochemical and molecular findings of 13 Japanese βUP deficient patients. In this group of patients, three novel missense mutations (p.G31S, p.E271K, and p.I286T) and a recently described mutation (p.R326Q) were identified. The p.R326Q mutation was detected in all 13 patients with eight patients being homozygous for this mutation. Screening for the p.R326Q mutation in 110 Japanese individuals showed an allele frequency of 0.9 %. Transient expression of mutant βUP enzymes in HEK293 cells showed that the p.E271K and p.R326Q mutations cause profound decreases in activity (≤ 1.3 %). Conversely, βUP enzymes containing the p.G31S and p.I286T mutations possess residual activities of 50 and 70 %, respectively, suggesting we cannot exclude the presence of additional mutations in the non‐coding region of the UPB1 gene. Analysis of a human βUP homology model revealed that the effects of the mutations (p.G31S, p.E271K, and p.R326Q) on enzyme activity are most likely linked to improper oligomer assembly. Highly variable phenotypes ranging from neurological involvement (including convulsions and autism) to asymptomatic, were observed in diagnosed patients. High prevalence of p.R326Q in the normal Japanese population indicates that βUP deficiency is not as rare as generally considered and screening for βUP deficiency should be included in diagnosis of patients with unexplained neurological abnormalities.